Teori Belajar Populer: Pendidikan Karakter Cerdas, Quantum Learning, Accelerated Learning - Herman, Pebriani Yusnia; Nirwana, Herman; N, Neviyarni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Learning difficulties may be caused by inappropriate teaching methods, inappropriate curriculum focus, or even complicated learning. Therefore, it is necessary to have an appropriate learning theory model that involves interaction during learning so that students are active. Many learning theory models can be applied in the learning process. However, all learning theory models have their advantages and disadvantages. Through popular learning theories, it is hoped that ineffective teaching and learning processes can be minimized. Some of the learning methods in popular learning theories that will be discussed this time are: intelligent character education, quantum learning and accelerated learning.